Hydrogen-Induced Phase Transformation and Microstructure Evolution for Ti-6Al-4V Parts Produced by Electron Beam Melting; Metals; Vol. 8, iss. 5 - Pushilina N. S. Natalia Sergeevna; Panin A. V. Alexey Viktorovich; Syrtanov M. S. Maksim Sergeevich; Kashkarov E. B. Egor Borisovich; Kudiyarov V. N. Victor Nikolaevich; Perevalova O. B. Olga Borisovna; Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Koptyug A. V. Andrey Valentinovich (2018, 2018)
Title screen